Forgotten Warsaw printing house of Hindemith brothers. The history and achievements - Walczak, Krzysztof (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The article brings back the history of the forgotten printing house founded in Warsaw by the sons of a well-known printer from Kalisz, Karol Wilhelm Hindemith. The printing house has left a lot of interesting publications despite of its short period of activity, which was interrupted by the unexpected death of one of the owners. The history of the forgotten printing house enriches the history of the 19th century printing in Warsaw.